Sustained benefit of zanubrutinib vs ibrutinib in patients with R/R CLL/SLL: final comparative analysis of ALPINE - Brown, Jennifer R; Eichhorst, Barbara; Lamanna, Nicole; O'Brien, Susan M; Tam, Constantine S; Qiu, Lugui; Jurczak, Wojciech; Zhou, Keshu; Šimkovič, Martin; Mayer, Jiří; Gillespie-Twardy, Amanda; Ferrajoli, Alessandra; et al. (Blood, 2024)
The ALPINE trial established the superiority of zanubrutinib over ibrutinib in patients with relapsed/refractory chronic lymphocytic leukemia and small lymphocytic lymphoma; here, we present data from the final comparative analysis with extended follow-up. Overall, 652 patients received zanubrutinib (n = 327) or ibrutinib (n = 325). At an overall median follow-up of 42.5 months, progression-free survival benefit with zanubrutinib vs ibrutinib was sustained (hazard ratio [HR], 0.68; 95% confidence interval [CI], 0.54-0.84), including in patients with del(17p)/TP53 mutation (HR, 0.51; 95% CI, 0.33-0.78) and across multiple sensitivity analyses. Overall response rate remained higher with zanubrutinib compared with ibrutinib (85.6% vs 75.4%); responses deepened over time with complete response/complete response with incomplete bone marrow recovery rates of 11.6% (zanubrutinib) and 7.7% (ibrutinib). Although median overall survival has not been reached in either treatment group, fewer zanubrutinib patients have died than ibrutinib patients (HR, 0.77 [95% CI, 0.55-1.06]). With median exposure time of 41.2 and 37.8 months in zanubrutinib and ibrutinib arms, respectively, the most common nonhematologic adverse events included COVID-19-related infection (46.0% vs 33.3%), diarrhea (18.8% vs 25.6%), upper respiratory tract infection (29.3% vs 19.8%), and hypertension (27.2% vs 25.3%). Cardiac events were lower with zanubrutinib (25.9% vs 35.5%) despite similar rates of hypertension. Incidence of atrial fibrillation/flutter was lower with zanubrutinib vs ibrutinib (7.1% vs 17.0%); no cardiac deaths were reported with zanubrutinib vs 6 cardiac deaths with ibrutinib. This analysis, at 42.5 months median follow-up, demonstrates that zanubrutinib remains more efficacious than ibrutinib with an improved overall safety/tolerability profile. This trial was registered at www.ClinicalTrials.gov as #NCT03734016.
Keywords: senioři; Adenine; senioři nad 80 let; výsledek terapie; Middle Aged; mužské pohlaví; adenin; Adult; Pyrimidines; pyrimidiny; Aged, 80 and over; chronická lymfatická leukemie; Pyrazoles; ženské pohlaví; Piperidines; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; lidé středního věku; pyrazoly; dospělí; piperidiny; Female; Aged; Treatment Outcome; lidé; Male